Safety Assessment of POLYSORB® ID a Fatty Acids-Diesters Isosorbide Used as a Plant-based Solutions for Plasticizers - Simar-Menti`eres, S.; Nesslany, F.; Sola, M. L.; Mortier, S.; Raimbault, J. M.; Gondelle, F.; Chabot, L.; Pandard, P.; Wils, D.; Chentouf, A. (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
Phthalate esters, mainly di-ethylhexylphthalate (DEHP), represent a class of chemicals primarily used as plasticizers for polyvinyl chloride in a wide range of domestic and industrial applications. These phthalate esters are low toxicity environmental contaminants. To address these drawbacks, POLYSORB® ID 37, a blend of diesters obtained from esterification of isosorbide with plant-based fatty acids, was developed. This article will describe the toxicological and biodegradability studies carried out to determine both the human and environmental risk assessments. Overall, all of the toxicological and biodegradability studies demonstrated that POLYSORB® ID 37 is non-toxic to mammalian life and is readily biodegradable.